IMPLEMENTASI PROTOKOL KYOTO DI BRASIL TERHADAP DEFORESTASI HUTAN AMAZON TAHUN 2000 – 2018 (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This study explains the reasons for Brazil to develop its beef cattle industry despite Brazil's ratification of the Kyoto Protocol. The Kyoto Protocol is an international agreement to reduce greenhouse gas emissions that have caused global warming. Development of the Brazilian beef cattle industry is an industry that causes deforestation in the Amazon forest. This activity has been able to place Brazil as the world's largest exporter of meat. The analysis described in this study attempts to explain the gap between the ratification of international treaties and their implementation in domestic policy. Method that is used is a qualitative research method with data collection techniques sourced from literature studies. As for the framework of thinking that becomes the reference for analysis in this study is the National Interest and Environment Kuznets Curve (EKC).